Photovoltaic Voltage Regulation through Distributed Power Compensation Considering Communication Delay. Issue 1 (31st October 2019) - Zhang, Zhanqiang; Dou, Chunxia; Yue, Dong; Zhang, Bo; Zhang, Tengfei
Abstract: To solve the overvoltage problem in high penetration photovoltaic (PV) system, a new voltage regulation method is proposed. First, the node voltage sensitivity to PV power is calculated. Next, an optimal power compensation scheme using a new compensation mechanism is obtained so that the node voltage can be acceptably regulated with minimum power curtailment. The maximum tolerable communication delay is also estimated based on PV power mutation during communication delay (CD). Because extreme learning machine (ELM) algorithms exhibit fast and precise prediction, they can be used here to predict PV power. Based on the predicted power, the power compensation can be appropriately corrected to achieve effective voltage regulation under abnormal CD (ACD). Finally, the results indicate that voltage deviation can be regulated to an acceptable range of 1.00–1.05 per unit by using the proposed power compensation approach to curtail reactive power or even active power. The maximum PV power error predicted by ELM algorithm is only 2.67%, which is an acceptable basis for power compensation correction under ACD. Hence, by curtailing additional PV power again, the effective voltage regulation can be finally ensured under power mutation with ACD. Abstract : To address the photovoltaic overvoltage issue, a distributed power compensation scheme is proposed. Its effectiveness under abnormal communication delay is ensured by a predictive compensation based on maximum tolerable communication delay estimation and an extreme learning machine algorithm. It is shown from the results that the proposed method possesses a good voltage regulation performance and communication security.